Where Are We With Human Lice? A Review of the Current State of Knowledge - Amanzougaghene, Nadia; Fenollar, Florence; Raoult, Didier; Mediannikov, Oleg (Frontiers in Cellular and Infection Microbiology, 2020)
Pediculus humanus is an obligate bloodsucking ectoparasite of human that includes two ecotypes, head louse and body louse, which differ slightly in morphology and biology, but have distinct ecologies. Phylogenetically, they are classified on six mitochondrial clades (A, B, C, D, E and F), head louse encompasses the full genetic diversity of clades, while body louse belongs to clades A and D. Recent studies suggested that not only body louse, but also head louse can transmit disease, which warrants greater attention as a serious public health problem. The recent sequencing of body louse genome confirmed that P. humanus has the smallest genome of any hemimetabolous insect reported to date, and also revealed numerous interesting characteristics in the nuclear and mitochondrial genomes. The transcriptome analyses showed that body and head lice were almost genetically identical. Indeed, the phenotypic flexibility associated with the emergence of body lice, is probably a result of regulatory changes, perhaps epigenetic in origin, triggered by environmental signals. Current lice control strategies have proven unsuccessful. For instance, ivermectin represents a relatively new and very promising pediculicide. However, ivermectin resistance in the field has begun to be reported. Therefore, novel opportunities for pest control strategies are needed. Our objective here is to review the current state of knowledge on the biology, epidemiology, phylogeny, disease-vector and control of this fascinating and very intimate human parasite.